Students' perspectives on teaching quality determinants: a comparative study between social sciences and pure sciences students in the northern region universities / Roshima Said ... [et al.] - Said, Roshima; Wan Omar, Maznah; Awang, Norasmila; Husin, Zaliha (Universiti Teknologi MARA, Kedah, 2004)
The present study seeks to determine the possible criteria that would affect the level of teaching quality among academicians of Institute of Higher Learning from the students' perspectives. Three universities in the Northern region were selected in this study, which include Universiti Teknologi MARA (UiTM) Kedah, Per/is and Pu/au Pinang Branch Campuses, Universiti Sains Malaysia (USM), and Universiti Utara Malaysia (UUM). A sample of 500 Social Sciences and Pure Sciences students from the three universities was selected for this study. The findings showed that the teaching quality determinants that are ranked as ve,y important to both social sciences and pure sciences students are as follows; Clarity, Feedback, Syllabus, Creativity, Practicality, Exercises, Attention, Enthusiasm, Availability, Approachable, Communication And Language Use. Moreover,- the social sciences students also perceived the other five determinants i.e Motivation, Extra Reading, Technology, Punctuality and Cu"ent Issues as ve,y important, while the pure sciences students perceived them as important except for current issues, which is perceived as not important.